Academic Service Management and Its Impact on Student Satisfaction in Higher Education - Kasirun, Kasirun; Awalludin, Awalludin; Wiyono, Sigit; Salsabila, Salsabila (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of academic service management on student satisfaction levels in higher education. Using a qualitative approach through in-depth interviews, observation, and document analysis, the study revealed that the quality of academic services is a key factor in shaping students' learning experiences. The results indicate that the implementation of digitalized services based on an integrated information system increases efficiency and transparency, in accordance with the principles of the Technology Acceptance Model (TAM). Furthermore, the proactive role of academic advisors in academic guidance and consistent communication through official channels also contribute to increased student satisfaction. Other findings identify the importance of continuous evaluation and improvement (Continuous Quality Improvement/CQI) based on student feedback, such as the development of a helpdesk and staff training. This study concludes that higher education institutions need to strengthen academic services through technology-based approaches, increased academic advisor capacity, and integrated communication systems. The practical implication is the need for policies oriented toward student-centered service to improve the quality of education holistically.